2020
DOI: 10.1248/bpb.b20-00605
|View full text |Cite
|
Sign up to set email alerts
|

Trends of the Use of Anti-methicillin-Resistant <i>Staphylococcus aureus</i> Agents in Japan Based on Sales Data from 2006 to 2015

Abstract: Patterns of the use of anti-methicillin-resistant Staphylococcus aureus (MRSA) agents in Japan might be influenced by the launch of new anti-MRSA agents, the publication of relevant guidelines, and the increase in the number of generic medicines. However, as anti-MRSA agents are included in multiple anatomical therapeutic chemical classifications, such as glycopeptides and aminoglycosides, the trends of the use of individual anti-MRSA agents remain unclear. Here, we aimed to clarify the trends of anti-MRSA age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…This is because all gentamicin products contain only 0.1% gentamicin. Although the AMU of oral and parenteral antibiotics have been evaluated by the amount of ingredient (1,8), it was suggested that topical AMU should be evaluated by the number of products.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because all gentamicin products contain only 0.1% gentamicin. Although the AMU of oral and parenteral antibiotics have been evaluated by the amount of ingredient (1,8), it was suggested that topical AMU should be evaluated by the number of products.…”
Section: Discussionmentioning
confidence: 99%
“…AMU is often studied using the insurance claims database and sales data (7,8). The National Database of Health Insurance Claims and Specific Health Checkups of Japan (NDB) is an insurance claim database that contains most of the available data in the national healthcare insurance system.…”
Section: Introductionmentioning
confidence: 99%
“…A study of anti-MRSA agent sales in Japan found that the ratio of oral linezolid to total linezolid rose from 25.5% to 39.9% between 2006 and 2015 [ 2 ]. Our study found that oral and sequential therapies might lead to more vomiting and diarrhea events than intravenous therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Linezolid is recommended as an alternative to vancomycin, a first-line drug, for treating resistant Gram-positive bacterial infections, such as MRSA osteoarthritis. With the increased use of anti-MRSA agents, the trend of vancomycin and linezolid use demonstrated a significant increase from 2006 to 2015 in Japan [ 2 ]. However, the safety and efficacy of linezolid in children remain understudied.…”
Section: Introductionmentioning
confidence: 99%
“…It is thought that this may reflect compliance with the guidelines, the launch of new anti-MRSA drugs, and less promotion of the original agents in Japan. Goto et al [ 17 ] reported on the trends of only anti-MRSA agent use in Japan based on sales data. The total anti-MRSA agent use was found to have significantly increased from 2006 to 2015 ( p for trend = 0.027).…”
Section: Antimicrobial Stewardship With Mrsa and Extended-spectrum β-Lactamase (Esbl)-producing Enterobacteriaceaementioning
confidence: 99%